Reduction of the variability of a water demineralization process by ion exchange; for the production of soft drinks. - Vasquez Reino, Edgar Walter (Enfoque UTE, 2018)
The focus of this work was to find the necessary solutions to reduce variability, increase capacity and establish a plan to improve the water demineralization process for beverage production. For this, the diagnosis of the process was made and the elements, supplies and equipment were physically recognized, from the taking of the source to the manufacture of the beverages. The critical quality variables were determined by quality control according to laboratory tests and historical data. It was established within the problematic that the two critical quality variables were the hardness and alkalinity of the water; the process was studied with the reference in these two variables to know the root causes that caused the problems, measurements were made to calculate the capacity of the process and perform stability analysis, and the root causes of the problem were determined. The improvement included staff training, start-up manual and equipment regeneration manual, as well as process controls through type X-R control charts. The reduction of variability, the increase in capacity and improvement of the process was achieved.